An overview of smallholder dairy farming in mixed mountain farming systems of the HKH: Issues and priorities - Tulachan, P.M.; Jabbar, M.A.; Mohamed-Saleem, M.A. (International Centre for Integrated Mountain Development, 2002)
A Geographic Information Systems (GIS) - based analysis of livestock population dynamics in the Hindu Kush-Himalayan (HKH) region conducted by the International Centre for Integrated Mountain Development (International Centre for Integrated Mountain Development) and the International Livestock Research Institute (ILRI) indicated that over the last 10-15 years considerable changes has been taking place in the structure and management systems of smallholder dairy farming in areas with a high concentration of dairy within mixed mountain farming systems. Recently there have been notable changes in the dairy population in terms of species and breeds, infrastructure and market Developments. Until now there has been little attempt to gather knowledge about the specific nature of these changes and transformations or how they have affected the sustainability of the smallholder dairy production systems and the lives of people. Further more the constraints on and opportunities for smallholder dairy Development in the different areas of the HKH are not well known. It is with the aim of filling these knowledge gaps and identifying priority areas for further research that International Centre for Integrated Mountain Development and ILRI planned a study on 'Market-oriented Smallholder Dairy in the Mixed Mountain Farming Systems' in four areas in three HKH countries - Bhutan, India, and Nepal. The aim of this paper is to explore the trends and patterns of dairy Development; to study the characteristics of smallholder dairy production and post-production systems; to identify the key socioeconomic, gender, and natural resource management issues related to smallholder dairy farming; and to identify policy and institutional issues for dairy Development.